Diversity analysis of oral and gut microbiota in osteoporotic rats - Mingzhu Chen; Zihan Liao; Zhenjin Yang; Yanjie Li; Liya Ma; Jiangtian Hu (PLoS ONE, 2025)
The oral and gut microbiota had been shown to control bone metabolism and have a strong correlation with osteoporosis. However, to reveal the oral and gut bacteria characteristics in osteoporosis, further studies are still needed to investigate the relationship between oral and gut microbiota diversity and bone health in OVX-induced osteoporotic rats versus Sham-operated (Sham) rats. This study analyzed the oral and gut microbiota in OVX and Sham rats using 16S rRNA gene sequencing. We compared microbial diversity and composition between the two groups. There was an inverse association found between the number of bacterial taxa and bone mineral density (BMD) readings. The OVX group had considerably higher estimated diversity of both oral and gut microbiota than the Sham group. Firmicutes, Bacteroidota, Proteobacteria, and Actinobacteriota were the dominant phyla in both groups. The OVX group had a reduced ratio of Firmicutes in oral and gut microbiota compared to the Sham group (p <  0.05). OVX rats had a higher proportion of oral Bacteroidota but a lower proportion of gut microbiota. They also had a substantial drop in Lactobacillus in both oral and gut microflora (p <  0.01). The crosstalk between oral and gut microbiota may be important in the development of osteoporosis. Identifying novel biomarkers in the oral and gut microbiota could provide more information in osteoporosis and the intricate oral-gut-bone health interaction.